Penguatan Literasi Membaca bagi Guru Matematika SMP Se-Kecamatan Moa dalam Menigkatkan Kualitas Pembelajaran - Dovila Johansz (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
Reading literacy skills are essential for all teachers, including mathematics teachers. Reading literacy is not only about the ability to comprehend texts but also plays a crucial role in supporting critical thinking, analytical reasoning, and problem-solving in the learning process. Acknowledging its importance, the author conducted a community service activity in the form of a training program aimed at strengthening reading literacy skills among junior high school mathematics teachers in Moa District. The training was held on Thursday, October 17, 2024, at the PSDKU Hall of Pattimura University, Southwest Maluku Regency Campus. A total of 17 junior high school mathematics teachers from Moa District participated in the activity.The training methods included the presentation of reading literacy materials in the context of mathematics learning, group discussions, and hands-on practice in analyzing and developing literacy-based math problems. The success of the training was measured using two instruments: a questionnaire assessing participants’ understanding of the material and a test measuring their reading literacy skills before and after the training. Data analysis revealed that participants generally felt they understood the material presented. Moreover, there was a noticeable improvement in their reading literacy skills following the training. These results indicate that the training was conducted effectively and achieved its intended objectives. This activity is expected to have a positive impact on improving the quality of mathematics instruction in schools by enhancing teachers' reading literacy as a key component in facilitating student learning.